DRAPING AS A METHOD OF FORMATION AND CREATIVE STAGE OF THE EDUCATIONAL PROCESS - Hasem, Amina (Theory and practice of design, 2023)
Purpose. The author sets himself the task of analyzing the methods of draping fabrics and ways of mastering them in the training process of clothing designers. And also – to investigate which means of draping the fabric become a form-forming component and the basis of the image of the suit. Methodology. On the example of student works from the discipline «Modeling plastic form of a suit», the author demonstrates the ways of using draping techniques, namely «origami» and «paper plastic», their influence as form-forming means of design, and as a method and sequence of making layouts in the material. Results. The justification of the topicality of the topic in scientific and professional literature was analyzed. Artistic and compositional means of form formation, methodology and stages of the educational process conditioned by the mastery of drapery techniques are systematized. The features of the methodical sequence of developing a costume form of a given structure by compositional and constructive means of form formation are considered. Form-forming means of drapery as a creative component of the educational process of creating clothing as a modern design product are substantiated. The scientific novelty of the research consists in the systematization of artistic and compositional means of form formation and in the comprehensive consideration of three-dimensional and spatial sketching of clothing models directly on the mannequin as a quick sketch – «volumetric sketching», as a platform for experiments and self-expression in modern clothing design. Practical relevance. The materials of the article are intended for use in the educational process in the training of fashion design specialists and stylists. They can also be used when writing scientific papers on the relevant subject. The results of the research can be useful for the development of modern clothing collections, both during professional training and in direct authorial design activities.